2013
DOI: 10.1007/s12031-013-0066-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 Genetic Polymorphism May Increase the Risk of Developing Leukoaraiosis in Chinese

Abstract: Cyclooxygenase-2 (COX-2) is a key enzyme involved in the conversion of arachidonic acid into prostaglandins, which are important mediators of inflammation. To clarify the role of inflammation in the pathogenesis of cerebral small vessel disease (SVD), we investigate the possible modulating effect of the functional COX-2 polymorphisms -1195G > A (rs689466) and -765G > C (rs20417) on the risk for development of cerebral SVD in a Chinese population. Genomic DNA of 116 patients with lacunar infarction (LI), 334 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The finding is in agreement with a recent case-control Chinese study showing an association between WMH and two functional COX-2 gene polymorphisms (rs20417 and rs689466)(23). White matter disease is a marker of small vessel disease and increases with aging and cumulative burden of cerebrovascular risk factors(12, 18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding is in agreement with a recent case-control Chinese study showing an association between WMH and two functional COX-2 gene polymorphisms (rs20417 and rs689466)(23). White matter disease is a marker of small vessel disease and increases with aging and cumulative burden of cerebrovascular risk factors(12, 18).…”
Section: Discussionsupporting
confidence: 93%
“…While adequately powered cohorts have suggested an association(1923), the most recent meta-analysis did not confirm prior findings(2). One potential explanation is that the association is highly dependent on the interaction with environmental factors affecting expression of the gene.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, 15 SNPs were included in the second group ( Table 1 ). Since they resulted in the missense changes, those SNPs were chosen from 28 SNPs which were reported to be related with the risk of WMHs or WMLs in previous candidate gene association studies amongst European or American individuals and listed in Supplemental Table 1 (Schmidt et al, 2000; Henskens et al, 2005; van Rijn et al, 2006; Fornage et al, 2007; Hogh et al, 2007; van Rijn et al, 2007; Taylor et al, 2008; Godin et al, 2009; Paternoster et al, 2009; Fernandez-Cadenas et al, 2011; Shan et al, 2013; Lin et al, 2015). Eleven of 28 SNPs were excluded from the present study since they were located in the non-coding regions of genes and considered to be non-functional SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the COX-2-765G>C polymorphism is a protective factor against ischemic stroke in Italians [34], but the association between COX-2-765G>C and ischemic stroke and leukoaraiosis could not be replicated in Chinese [27,38] and Koreans [39]. As for COX-2-8473T>C, Maguire et al [40] demonstrated a significant effect of the COX-2-8473T>C polymorphisms on ischemic stroke functional outcome in Australians, while no association between the COX-2-8473T>C polymorphisms and intracerebral hemorrhage was observed in Koreans [41].…”
Section: Plos Onementioning
confidence: 99%